Correlating Structural Features and 207Pb NMR Parameters with the Stereochemical Activity of PbII Lone Pairs in Birefringent Pb[2, 6‐bis(benzimidazol‐2‐yl)pyridine] Complexes. Issue 1 (30th November 2016) - Thompson, John R.; Snider, David; Wren, John E. C.; Kroeker, Scott; Williams, Vance E.; Leznoff, Daniel B.
Abstract : A series of Pb II materials containing the highly anisotropic tridentate ligand 2, 6‐bis(benzimidazol‐2‐yl)pyridine (bbp) and [Au(CN)2 ] –, Hg(CN)2 or halide bridging units, [Pb(bbp)Br2 ]· 2H2 O, Pb(bbp)I2, [Pb(bbp)I]2 (µ‐I)[Au(CN)2 ], [Pb(bbp)Br]2 (µ‐Br)[Au(CN)2 ], [Pb(bbp)Br2 ][Hg(CN)2 ], Pb(bbp)Cl[Au(CN)2 ]· 0.25H2 O and Pb(H2 O)(bbp)2 [Au(CN)2 ]2, have been prepared, structurally characterised and investigated spectroscopically by 207 Pb solid‐state NMR spectroscopy. Of these, five possess similar coordination geometries, providing an ideal series to investigate structural parameters as indicators for stereochemical activity by correlation with the 207 Pb chemical shift span parameter ( Ω ). The bond length of the substituent opposite to the stereochemically active lone pair and the angle between axial ligands were found to correlate weakly with Ω for these compounds ( R 2 = 0.85 and 0.66, respectively) and an expanded set of compounds with varying components and structures ( R 2 = 0.60 and 0.67, respectively), which indicates that these (or similar) structural parameters or Ω can be used to estimate the degree of lone‐pair activity. Compounds were also found to be highly birefringent with values ranging from 0.31(5) for Pb(H2 O)(bbp)2 [Au(CN)2 ]2 to 0.660(4) for [Pb(bbp)Br2 ]· 2H2 O, the latter being amongst the most birefringent compounds reported. Abstract : A set of highly birefringent Pb(bbp) [bbp = 2, 6‐bis(benzimidazol‐2‐yl)pyridine] complexes has been investigated by 207 Pb solid‐state NMR spectroscopy and X‐ray crystallography, showing correlations between two structural distortion parameters and the 207 Pb chemical shift span, which allows the relative degree of stereochemical lone‐pair activity of each complex in the series to be determined.